2016
DOI: 10.18632/oncotarget.10477
|View full text |Cite
|
Sign up to set email alerts
|

The bile acid receptor GPBAR1 (TGR5) is expressed in human gastric cancers and promotes epithelial-mesenchymal transition in gastric cancer cell lines

Abstract: GPBAR1 (also known as TGR5) is a bile acid activated receptor expressed in several adenocarcinomas and its activation by secondary bile acids increases intestinal cell proliferation. Here, we have examined the expression of GPBAR1 in human gastric adenocarcinomas and investigated whether its activation promotes the acquisition of a pro-metastatic phenotype. By immunohistochemistry and RT-PCR analysis we found that expression of GPBAR1 associates with advanced gastric cancers (Stage III-IV). GPBAR1 expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…Epithelial-mesenchymal transition (EMT) is a biological process in which epithelial cells are transformed into mesenchymal-like cells under certain physiological or pathological conditions (6,7). It has been suggested that EMT serves a key function in tumor invasion and metastasis (8). Future studies investigating the molecular mechanism underling EMT in tumor invasion and metastasis are required.…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) is a biological process in which epithelial cells are transformed into mesenchymal-like cells under certain physiological or pathological conditions (6,7). It has been suggested that EMT serves a key function in tumor invasion and metastasis (8). Future studies investigating the molecular mechanism underling EMT in tumor invasion and metastasis are required.…”
Section: Introductionmentioning
confidence: 99%
“…(33) Up-regulation of TGR5 was also reported in patients with cholangiocarcinoma and pancreatic cancers. (21,33) Thus, there appears to be a growing number of diseases (17,21,23,32) in addition to PLD in which an effective antagonist to TGR5 might be of value.…”
Section: Discussionmentioning
confidence: 99%
“…TGR5 agonists are known to affect downstream signaling events through coupling to Gα s , Gα i , and Gα q proteins . Moreover, stimulation of TGR5 in different cell types, including cholangiocytes, has been shown to increase cAMP and affect cell proliferation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TGR5 activation may promote cholangiocyte proliferation to increase the risk of cholangiocarcinoma 11. Recently, TGR5 was shown to be expressed in human gastric cancer,12 although this finding was controversial compared to data from a previous report 13. Therefore, questions remain regarding the essential role of TGR5 inhibition in clinical applications.…”
Section: Introductionmentioning
confidence: 99%